Species composition and size distribution of fishes in mangrove ecosystems in Kendari and Staring Bays, Southeast Sulawesi, Indonesia - LATIFA FEKRI; KANGKUSO ANALUDDIN; YUSNAINI YUSNAINI; HASAN ELDIN ADIMU; ANDI CHADIJAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Fekri L, Analuddin K, Yusnaini, Adimu HE, Chadijah A. 2024. Species composition and size distribution of fishes in mangrove ecosystems in Kendari and Staring Bays, Southeast Sulawesi, Indonesia. Biodiversitas 25: 3683-3692. Mangrove ecosystem plays very important role in supporting marine organisms including fishes, shells, etc. This study aimed to determine the species composition and size distribution of fishes living around the mangrove ecosystems in Kendari and Staring Bays, Southeast Sulawesi, Indonesia. Fish samplings were conducted using 6 gill nets fishing gear with mesh sizes of 1, 1.5 and 2 inches. Mangrove species composition was sampled using circular plots with diameter of 14 m. The fish conservation status and abundance were determined, while size distribution was analyzed in terms of frequency distribution of body weight, and correlation of body weight and body length. A total of 33 fish species were recorded across the two sampling sites with 30 species were found in Kendari Bay and 19 species were found in Staring Bay. The fish species are mostly classified as least concern based on the IUCN Red List. We found that species richness, presence and abundance of fishes varied according to the moon lightness periods during the fish catchments. The highest species richness was found in the dark moon both in Kendari and Staring Bays, while the lower fish richness was found in the transition from the dark to the full moon in Kendari Bay and the transition from the full moon to the dark moon in Staring Bay. Five fish species associated with mangroves of Kendari and Staring Bays were found more abundant and showed different size distribution pattern, i.e., normal shape of size distribution for Zenarchopterus dispar (Valenciennes, 1847), Ambassis dussumieri Cuvier, 1828 and Upeneus moluccensis Bleeker, 1855, while Mugil cephalus Linnaeus, 1758 and Acentrogobius viridipunctatus Valenciennes, 1837 showed L-shaped size distribution. These five dominant fishes showed well allometric relationships of body length and weight. Our findings suggested that mangrove ecosystems in Kendari and Staring Bays play an important role in maintaining fish diversity.